Determination of Plasminogen in Clots and Thrombi - Hedner, Ulla; Nilsson, Inga Marie; Robertson, B (Thrombosis and Haemostasis, 1966)
The plasminogen content was determined by a casein method in plasma and serum from 20 normal volunteers. The mean plasminogen content was found to be 10.1 ACU (the arbitrary caseinolytic unit defined in such a way that using a 3% casein solution and a digestion time of 20 min. at 37°C, 10 ACU gave an extinction of 0.300). No difference between serum and plasma regarding the plasminogen content was found.Plasminogen was determined in drained and drained plus washed clots prepared from 2 ml plasma. The highest values found in the drained clots were 0.9 ACU/clot and 0.2 ACU/clot in the drained plus washed clots.Plasminogen was also determined in drained and drained plus washed clots prepared from plasma with added purified plasminogen. The plasminogen was recovered in the washing fluid. According to these tests, then, purified added plasminogen is washed out of the clots.The plasminogen content of 20 thrombi obtained post mortem was also determined. The mean value was found to be 0.7 ACU/cm thrombus. Judging from our results, the “intrinsic clot lysis theory” is not the main mechanism of clot dissolution.